Cryptocurrency Assets As Inheritance Objects And Legal Protection For Cryptocurrency Holders In Indonesia From The Perspective Of Civil Law - Indra, Joe Aprella; Urbanisasi, Urbanisasi (Universitas Ibn Khaldun Bogor, 2025)
The development of digital technology has triggered a significant transformation in the economic and asset ownership system, particularly with the emergence of cryptocurrency. In Indonesia, digital assets such as Bitcoin and Ethereum are gaining popularity as tools for investment and wealth storage. As public adoption increases, the legal need to regulate cryptocurrency’s status as inheritable property becomes more urgent. However, Indonesia's civil inheritance law does not explicitly recognize cryptocurrency as part of an estate, leading to a legal vacuum that causes uncertainty in ownership rights and legal protection for heirs. This study uses a normative juridical approach and literature analysis to explore the legal status of cryptocurrency as an inheritance object and propose forms of legal protection for cryptocurrency holders. The findings indicate that although cryptocurrency fulfills the criteria of intangible, transferable, and economically valuable assets, formal mechanisms for inheritance transfer are lacking. Key issues include loss of private keys, inheritance disputes, and absence of adaptive legal instruments. Regulatory reforms are needed through digital wills, electronic authentication systems, and the role of digital notaries to ensure asset security and legal certainty.